2023
DOI: 10.1103/physrevlett.130.028101
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy-Induced Convection Driven by Frontal Polymerization

Abstract: In this work, we study the interaction between a self-sustaining exothermic reaction front propagating in a direction perpendicular to that of gravity and the buoyancy-driven convective flow during frontal polymerization (FP) of a low-viscosity monomer resin. As the polymerization front transforms the liquid monomer into the solid polymer, the large thermal gradients associated with the propagating front sustain a natural convection of the fluid ahead of the front. The fluid convection in turn affects the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…24 It is unlikely that the FS addition is affecting the front velocity as previous reports show front kinetics are unaffected above a critical minimum viscosity to overcome convective effects. 17,35,36 It was also found that front velocity would increase with filler loading at a 1.5 mm thick layer, as shown in Figure 4b,d. The wooden mold used in the previous experiments has a thickness of 6 mm, which is much thicker than the actual diameter of the resin when it is extruded from the printer.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…24 It is unlikely that the FS addition is affecting the front velocity as previous reports show front kinetics are unaffected above a critical minimum viscosity to overcome convective effects. 17,35,36 It was also found that front velocity would increase with filler loading at a 1.5 mm thick layer, as shown in Figure 4b,d. The wooden mold used in the previous experiments has a thickness of 6 mm, which is much thicker than the actual diameter of the resin when it is extruded from the printer.…”
Section: Resultsmentioning
confidence: 70%
“…Studies of other carbon fiber composites have used plies of woven carbon fibers to witness an increase in front velocity due to thermal conductivity. , The thermal conductivity of milled carbon fibers is lower, 6.4 W m –1 K –1 , than carbon nanofibers, 1950 W m –1 K –1 . It is unlikely that the FS addition is affecting the front velocity as previous reports show front kinetics are unaffected above a critical minimum viscosity to overcome convective effects. ,, …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frontal polymerization (FP) , is an energy-efficient alternative manufacturing mode for thermoset polymers and composites, which require large amounts of energy for thermal processing in a pressurized autoclave . In contrast, FP is a self-propagating polymerization reaction that requires only a small, localized energy input for initialization, typically delivered by a heated tip or wire. ,, After initiation, heat is generated by the exothermic polymerization reaction and propagated by conduction and convection. , FP was initially described using acrylate chemistry, but it has since been demonstrated using many other monomers, although largely within the acrylate family . In this work, we focus on polymerizing dicyclopentadiene (DCPD), in which FP proceeds by frontal ring-opening metathesis polymerization (FROMP). …”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 After initiation, heat is generated by the exothermic polymerization reaction and propagated by conduction and convection. 4,6 FP was initially described using acrylate chemistry, but it has since been demonstrated using many other monomers, although largely within the acrylate family. 4 In this work, we focus on polymerizing dicyclopentadiene (DCPD), in which FP proceeds by frontal ring-opening metathesis polymerization (FROMP).…”
Section: ■ Introductionmentioning
confidence: 99%